Financial Inclusion and the Stability of Monetary Policy: Evidence from Asian Low- middle Income Countries - Minh, Ngo Ngoc; Loc, Nguyen Duc (International Journal of Psychosocial Rehabilitation, 2020)
The paper uses principal component analysis (PCA) to build financial inclusion index (FII). Then, the study runs the Pooled ordinary least square (POLS), fixed effect model (FEM), random effect model (REM) to examine the effect of financial inclusion (FI) on monetary policy in Asian low-middle income countries over the data for the period of 2008-2018. The robustness of the model is tested by generalized least square (GLS). The empirical results show that FI effects significantly on monetary policy. Accordingly, increasing the level of financial inclusion will reduce inflation, contributing to price stability and macroeconomic development.